Heterogeneity Impacts Urban Roughness for Earth System Modeling - Liu, Shaofeng; Shi, Qingche; Li, Lingke; Yuan, Hua; Wei, Zhongwang; Wei, Nan; Lu, Xingjie; Zhang, Shupeng; Li, Xian‐Xiang; Dai, Yongjiu (Geophysical research letters, 2025)
Displacement height (d $d$) and, particularly, roughness length (z0 ${z}_{0}$) are essential urban aerodynamic parameters for earth system modeling the climatic impact of urbanization. Urban heterogeneities, inherent to real cities and impacting significantly the transfer of energy, mass and momentum, are missing or empirically represented without physical basis in the current aerodynamic parameterizations. We propose to account for urban heterogeneities by applying multi‐layer division and the drag‐force approach jointly to urban canopies. The impact of urban heterogeneities is represented by vertical profiles of roughness density to form a physics‐based aerodynamic parameterization for real urban surfaces (denoted RUR). Evaluation over real urban surfaces shows that RUR generally outperforms the classical schemes, especially for the estimate of z0 ${z}_{0}$. The enhanced estimates of z0 ${z}_{0}$ from RUR can significantly improve surface flux estimation, especially for relatively rough urban surfaces. This indicates the potential to advance earth system modeling research on the climatic impact of urbanization. Plain Language Summary Roughness length and displacement height are essential urban aerodynamic parameters for modeling the impact of urbanization on regional climate and extreme weather in earth system models, as well as for analyzing city‐scale wind loads and pollutant dispersion. Real cities are complex, and their urban surfaces inherently heterogeneous. Urban heterogeneities, which impact significantly the transfer of energy, mass and momentum, are missing or empirically represented without physical basis in the current aerodynamic parameterizations (of roughness length and displacement height). In this study, we propose to account for urban heterogeneities by dividing buildings into multiple layers and partitioning the total wind drag for layers. The impact of urban heterogeneities is represented by vertical profiles of roughness density and a physics‐based aerodynamic parameterization for real urban surfaces (denoted RUR) is then developed. Performance of the RUR scheme was evaluated over real urban surfaces by using the data from two Japanese metropolises. In short, the physically based aerodynamic parameterization for real cities introduced in this study performs well and, with the availability of global high‐resolution urban morphology data, has the potential to significantly advance earth system modeling research on the climatic impact of urbanization. Key Points Buildings of a complex urban area are divided into multiple layers and the total drag is partitioned for layers to account for heterogeneity A scheme for the aerodynamic roughness length of complex urban surfaces is proposed based on the drag partition The proposed aerodynamic scheme is examined and through machine learning the physical mechanisms are evaluated over real urban surfaces